State‑of‑the‑art modification, mechanistic insight and breakthrough curve analysis of chitosan scaffolds for sustainable heavy metal adsorbent - Zubir, Aisyah; Abdullah, Erna Normaya; Danial, Wan Hazman; Goh, Pei Sean; Mat Piah, Mohd Bijarimi; Show, Pau-Loke; Ismail, Ahmad Fauzi; Ahmad, Mohammad Norazmi (Springer Nature, 2026)
Heavy metals are toxic, non-biodegradable pollutants that can persist in the environment and pose serious threats to human health and aquatic ecosystems. Industrial discharge of heavy metal-containing effluents continues to degrade water quality, highlighting the urgent need for effective and sustainable remediation methods. Among various techniques, adsorption stands out for its high efficiency, low cost, and reusability. Chitosan, a biopolymer derived from renewable and abundant sources, has gained significant attention as a promising biosorbent for heavy metal removal. However, its poor acid stability and limited number of active adsorption sites can hinder its performance. This review discusses recent advancements aimed at enhancing chitosan’s adsorption capacity and stability, focusing on three main strategies: (i) structural modification via crosslinking and grafting, (ii) selectivity improvement using the Hard and Soft Acid–Base (HSAB) theory, and (iii) optimization of operational parameters such as pH, contact time, and metal ion concentration. In addition, the adsorption mechanisms, including complexation, electrostatic interactions, and ion exchange, along with breakthrough curve analysis are explored to understand dynamic adsorption behavior. Importantly, this study also covers regeneration techniques, evaluating the reusability of modified chitosan across multiple cycles, cost analysis to assess economic feasibility, and findings from pilot-scale studies that demonstrate real-world applicability. Overall, this review provides a comprehensive guide for the development of efficient, cost-effective, and scalable chitosan-based adsorbents, contributing to the advancement of sustainable heavy metal remediation technologies.